2016
DOI: 10.3390/app6030084
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plastic Strain Energy and Acoustic Emission Energy in Reinforced Concrete Structures

Abstract: This paper presents a comparison of the acoustic emission (AE) energy and the plastic strain energy released by some reinforced concrete (RC) specimens subjected to cyclic or seismic loadings. AE energy is calculated, after proper filtering procedures, using the signals recorded by several AE low frequency sensors (25-100 kHz) attached on the specimens. Plastic strain energy is obtained by integrating the load displacement curves drawn from the measurements recorded during the test. Presented are the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…It is shown that as the corrosion level becomes higher (from Control to LC and HC beam specimens), there is a collective increase in AF and a decrease in RA value of the beam specimens. On the other hand, it also indicates the transition of the beam specimen dominating fracture behaviour, which shifts from tensile to shear as the damage stage increases (from damage Stage I to IV) in accordance to the classification method suggested previously[10,27,35]. RA value versus AF for (a) Control, (b) LC and (c) HC beam specimens4.2.2.…”
supporting
confidence: 84%
“…It is shown that as the corrosion level becomes higher (from Control to LC and HC beam specimens), there is a collective increase in AF and a decrease in RA value of the beam specimens. On the other hand, it also indicates the transition of the beam specimen dominating fracture behaviour, which shifts from tensile to shear as the damage stage increases (from damage Stage I to IV) in accordance to the classification method suggested previously[10,27,35]. RA value versus AF for (a) Control, (b) LC and (c) HC beam specimens4.2.2.…”
supporting
confidence: 84%
“…With the recent advances in structural health monitoring (SHM) [2][3][4][5][6][7][8] and nondestructive evaluation (NDE) [9,10], many monitoring and evaluation methods, such as modal characteristics-based methods [11][12][13], active sensing [14][15][16][17][18][19][20], electromechanical impedance [21][22][23][24][25], ultrasonic guided wave [26], active thermography [26][27][28] and vibrothermography [29,30], among others, are available. Among them, acoustic emission technique [31][32][33][34][35][36][37] is an effective nondestructive technique that can characterize the wear process [38,39], and it has been widely used in civil engineering [40][41][42][43], mechanical engineering [44][45][46][47]<...>…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other non-destructive testing approaches, using a highly sensitive piezoceramic probe, the AE technique is more sensitive to material damage, and it is suitable for continuous health monitoring in real time [17]. For example, researchers have extensively applied AE techniques to monitor concrete structures [43,[64][65][66][67][68]. Aldahdooh et al [41] and Prem et al [69] demonstrated that AE technique was an effective technique to monitor the damage process of reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Crack detection, hydration monitoring and energy harvesting using similar embedded piezoelectric transducers were reported in [6][7][8]. Recently, good correlation between acoustic emission energy at low frequency (25-100 kHz) and plastic strain energy of reinforced concrete specimens was established in [9,10]. An active acoustic method at a lower frequency of around 6 kHz was also employed [11] to monitor setting and hardening in concrete at early ages, wherein the P-wave velocity and attenuation coefficient were used to characterize the development of calcium silicate hydrate (C-S-H) gel inside the concrete and, hence, predict strength growth during early ages.…”
Section: Introductionmentioning
confidence: 96%